SAT0051 Cox-2 specific inhibition with mk-0663 120 mg q. d. over 4 weeks did not increase faecal blood loss: a controlled study with placebo and ibuprofen 800 mg t.i.d. (1st June 2001) - Hunt, RH; Callegari, P; Bowen, B; James, C; Marshall, J; Mortensen, E; Cagliola, A; Yu, C; Quan, H; Simon, T
Abstract : Background: Treatment with existing NSAIDs is associated with increased gastrointestinal microbleeding. We conducted a double-blind, single centre study in 62 healthy volunteers (age 19–33 years) to test the hypothesis that faecal blood loss with MK-0663 (a new highly selective COX-2 inhibitor with a selectivity ratio of >100 in human whole blood assay) would be equivalent to placebo and superior to ibuprofen. Objectives: To compare faecal blood loss in volunteers taking MK-0663, ibuprofen, or placebo. Methods: Subjects were injected with 51 Cr labelled red blood cells and daily faecal blood loss in collected stool was measured by a large sample counter. Subjects with normal faecal blood loss during a 1-week placebo baseline period were randomised to MK-0663 120 mg q.d., ibuprofen 800 mg t.i.d. or placebo treatment for 28 days. The effects of MK-0663 and placebo were compared by a predefined similarity bound for determination of equivalence. Results: The mean daily faecal blood loss (mL/day) over time is shown in the table below. MK-0663 (120 mg) was equivalent to placebo and caused less blood loss than ibuprofen. All treatments were generally well tolerated. Conclusion: In this study, the highly selective COX-2 inhibitor, MK-0663, at a dose twice that maximally effective in osteoarthritis, was equivalent to placebo, whereas a therapeutic dose of ibuprofen significantly increased faecal blood loss.